PERAN IDENTIFIKASI DAN ASESMEN PESERTA DIDIK DALAM MEWUJUDKAN PEMBELAJARAN BERKEADILAN DI SEKOLAH INKLUSIF - FUAD ABDULLAH; DESI SUSANTI (FKIP Universitas Wiraraja, 2026)
Inclusive education requires the implementation of equitable learning for all students, including those with special educational needs. One of the key components in realizing equitable learning is the systematic and continuous implementation of student identification and assessment. This study aims to examine and analyze the role of student identification and assessment in supporting equitable learning in inclusive schools. The study employed a literature review approach by analyzing relevant national and international journal articles, reference books, and policy documents published within the last five to seven years. Data were analyzed through organizing, categorizing, and synthesizing literature findings based on major themes, namely the role of student identification, continuous assessment, and their implications for the planning and implementation of inclusive learning. The findings indicate that identification and assessment play a strategic role in understanding students’ characteristics, initial abilities, and individual learning needs. Continuous diagnostic and formative assessments assist teachers in designing adaptive, differentiated, and non-discriminatory learning practices. In addition, teacher competence and collaboration among stakeholders are crucial factors in the successful implementation of identification and assessment. Therefore, strengthening comprehensive and sustainable identification and assessment practices is essential to support the realization of equitable inclusive learning,